Resor Pulau Setanau Pada Gugusan Pulau Tiga Di Natuna Dengan Pendekatan Arsitektur Pesisir (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Setanau Island is one island that is unsettled and located at Pulau Tiga Subdistrict, Natuna regency. Setanau Island has the potential to be visited by tourists, both local and foreign tourists. Therefore is needed accommodation tourist activity on the island of Setanau. The concept of Setanau Island Resort was designed by "Pearl", which is implementation form Natuna regency vision as a district that has a natural wealth worth selling. Pearl concept is applied through a transformation by analogy approach forms the pearl applied in the design of landscape patterns resort area. Designing Setanau Island resort also adopts the principle of Island Coastal Architecture Setanau. The principle was applied to the mass of the building in terms of both use of materials, orientation of buildings and structures. Application of the principle building aims to produce a coastal resort while maintaining, preserving, as well as to introduce hallmark Setanau Island Keywords: Resort, Setanau Island, Coastal Architecture